THE ANALYSIS OF MAJOR GRAMMATICAL ERRORS IN STUDENTS’ WRITING - Paramita, Paulina Erawati (IKIP PGRI Pontianak, 2016)
This study investigates and classifies grammatical errors in writing made by year nine students at SMP Gembala Baik Bilingual Class. The samples of this research were 30 students randomly selected from 61 students. Descriptive qualitative was used to describe the errors made by the 30 students. They were asked to write about their holidays, and then the analysis was conducted to see the errors found in their writings. The results show that There were three errors in noun endings, two errors in subject-verb agreement, four errors in verb tense, four errors in verb form, eight errors in capitalization, six errors in sentence fragment, and two errors in comma errors. The information of the types of students’ errors can be used as a guidance to evaluate the weakness or progress of students’ ability in learning English, particularly in writing.Keywords: grammatical errors, error analysis, contrastive analysis, English learning.